COVID 19 fatalities burden in Asian countries: An analysis of pattern and determinants. Issue 1 (2023) - Panda, Prasant Kumar; Varkey, Rittu Susan; Ranjan, Priya; Meher, Ashish Kumar; Panda, Soumyaranjan
Abstract: Covid 19 pandemic has severe implications on health and life of people. Asia being the most populous region has higher fatalities burden. Health infrastructure, stringent preventive measures by the government and public participation through adhering to social distancing have influence to check on fatalities' burden. The level of Social capital as well as voters' participation in a particular country can have influence on containment of COVID cases and fatalities. In this context, the main objectives of this study are to analyse pattern and trend of death burden for 45 Asian countries and impact of stringency measures by government, and voters' turnout ratio on death burden. However, for regression analysis only 32 countries are taken into account considering the availability of data for all variables. Multiple linear regression analysis is employed in a cross-sectional framework and Ordinary least square estimation technique with heteroscedastic adjusted standard errors have been used for estimation of coefficients. The results show that southern Asia contributes the highest share of fatality cases in total fatality cases of Asia with 71.43% share. It also has the highest share of confirmed cases in total confirmed cases of Asia with 71.72%. However, when we take the population into account, Western Asia leads in the share of confirmed COVID-19 cases and its associated fatality cases per million populations in Asia as compared to other Asian regions. The factors like health infrastructure and voters' turnover ratio are found to be significant and potential in reducing the new deaths per million populations. Though the coefficient of Stringency index has been negative and it did not emerge to be significant in Asian countries. The COVID related fatalities in Asian region are urban centric and urbanization proxy is found to be positive and significant. Diabetes prevalence rate has some heterogeneous result and in the present study its coefficient is not in the hypothesized direction. . The Countries should ramp up health infrastructure and necessary preparedness to deal with the subsequent waves and COVID related fatalities. Importance need to be given people's participation and their shared responsibilities in dealing with COVID cases and checking on fatalities. The realisation of social responsibility among the masses can lead to community participation and adhering to the protocols imposed by the government and helps in checking on spread of virus and associated death.